2017
DOI: 10.1186/s12913-017-2162-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective enrollment in Disease Management Programs for coronary heart disease in Germany – An analysis based on cross-sectional survey and administrative claims data

Abstract: BackgroundIn 2002, Disease Management Programs (DMPs) were introduced within the German healthcare system with the aim to increase the quality of chronic disease care. Due to the enrollment procedures, it can be assumed a) that only certain patients actively decide to enroll in a DMP and/or b) that only certain patients get the recommendation for DMP enrollment from their physician. How strong this assumed effect of self- and/or professional selection is, is still unclear.MethodsWe used data from a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Similar results (enrollment rate of 72%) were found throughout Germany in 2013 by Röttger et al [23] in patients with coronary heart disease. Possible explanations could be regional socio-economic differences and health characteristics of the respective cohorts as well as the time span between the studies [21,23]. In conclusion, it is apparent that the DMPs cannot reach their required target group in Saxony-Anhalt.…”
Section: Association Between Participation In Dmp or Cr After Ami Andsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results (enrollment rate of 72%) were found throughout Germany in 2013 by Röttger et al [23] in patients with coronary heart disease. Possible explanations could be regional socio-economic differences and health characteristics of the respective cohorts as well as the time span between the studies [21,23]. In conclusion, it is apparent that the DMPs cannot reach their required target group in Saxony-Anhalt.…”
Section: Association Between Participation In Dmp or Cr After Ami Andsupporting
confidence: 86%
“…It is also remarkable, that the proportion of enrollment in DMP of about one quarter is substantially lower than the 77%, which was found eight years ago in a comparable study in the region of Augsburg by Laxy et al [16]. Similar results (enrollment rate of 72%) were found throughout Germany in 2013 by Röttger et al [23] in patients with coronary heart disease. Possible explanations could be regional socio-economic differences and health characteristics of the respective cohorts as well as the time span between the studies [21,23].…”
Section: Association Between Participation In Dmp or Cr After Ami Andmentioning
confidence: 54%
See 1 more Smart Citation
“…As regards coordinated care programmes, the German disease-management programmes were implemented as policy initiatives 15 years ago and showed promising results in several evaluations [62,64]. However, an analysis recently revealed that characteristics such as male sex, increased age and receiving a pension were associated with higher odds for enrolment in these programmes [101]. For policy makers, this is important on two counts: on the one hand, these results show that the effectiveness of structured care programmes may differ between certain subpopulations, on the other hand, they highlight a need to ensure equal odds for the enrolment of different groups.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Contrary to other countries, in which DMPs were implemented with a focus on scientific evidence, in Germany, DMP rollout was accompanied by an elaborate legal framework that involved quality-of-care requirements, a strict accreditation process, and strong financial incentives for statutory health insurance funds to set up programs [14]. Five studies [15][16][17][18][19] evaluated CAD DMPs in Germany all using survey data. These studies assessed influence of patient characteristics [15], educational attainment and area deprivation [16], or the horizontal inequity indices and socio-economic status [17] on DMP enrollment.…”
Section: Introductionmentioning
confidence: 99%